TAIGA-HiSCORE: a new wide-angle air Cherenkov detector for multi-TeV gamma-astronomy and cosmic ray physics ... - Porelli, Andrea (Humboldt-Universität zu Berlin, 2020)
Der TAIGA Detektor (“Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy”) testet eine neue Nachweismethode der erdgebundenen Cherenkov Gamma Astronomie fuer 10TeV bis einige PeV, und fuer kosmische Strahlung oberhalb 100TeV: die Kombination abbildender und nicht-abbildender Cherenkov Detektoren in einem hybriden System. Im Fokus der Arbeit steht TAIGA-HiSCORE - ein Cherenkov Detektorfeld mit grosser Apertur zur Messung der Zeitstruktur der Cherenkovlichtfront in atmosphaerischen Luftschauern (EAS). Die Praezisonsvermessung der Schauerrichtung basiert auf (1) sub-nsec Zeitsynchronisation aller Detektoren, und (2) einer neuentwickelten Zeitkalibrationsmethode. Die Genauigkeit wird bestimmt mit experimentellen und simulierten EAS-Daten, spezieller LED-Kalibration und dem LIDAR Laserstrahl aus der International Space Station (ISS). Mit den HiSCORE9 Daten (2013-2014) wird die sub-nsec Zeitsynchronisation durch das White Rabbit Zeitsystem unter realen Bedingungen nachgewiesen. Eine neue, auch ... : The TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) detector is a new ground-based Cherenkov detection technology for gamma-astronomy from 10TeV up to several PeV, and cosmic rays (CR) above 100TeV. The main topic of this work is TAIGA-HiSCORE, the wide-aperture air Cherenkov timing array. The focus is on precision extensive air shower (EAS) arrival direction reconstruction, achieved by (1) sub-nsec time-synchronization between the array stations, and (2) a newly developed array time calibration procedure. The performance is verified using simulated and experimental data from EAS, dedicated LED calibration, and a LIDAR laser beam from the International Space Station (ISS). The analysis of the HiSCORE 9 data (2013-14), collected with a data acquisition system (DAQ) based on the White Rabbit (WR) timing system, allows to verify the sub-nsec time synchronization between the array stations. The analysis of HiSCORE 28 data (2015-2018) addresses the problem of achieving an ...